AKTIVITAS SITOTOKSIK SENYAWA Α-TERPINEOL PADA CELL LINE KANKER LEHER RAHIM (SEL HeLa) SEBAGAI SUMBER BELAJAR BIOLOGI MATERI POKOK BIOLOGI SEL - Rasuane Noor (Bioedukasi Jurnal Pendidikan Biologi, 2012)
α-terpineol is a compound of the class of  terpenoid  alcohols  derived  from natural  materials, α-terpineol can be synthesized from  α-pinene  from  turpentin content of extracts derived  from  the sap of  pine  trees  (Pinus merkusii). α-terpineol has been reported as a natural compound that has potential as anticancer agent. Objectives of research:  In general, to assess the activity of α- terpineol  compounds  against  HeLa  cells  and  the   possible  mechanism,  whereas  specifically  assessing  cytotoxic  activity. Methods: This was a quasi-experimental study using post-test only with non-equivalent control group design.  This study was conducted on HeLa cells by administering α-terpineol. Observations  cytotoxic   activity assay was performed using MTT assay method. Results: α -terpineol was cytotoxic against HeLa cells with IC50 of 12,46 μg/mL, therefore this compound was a potential anticancer   Kata kunci :  α-terpineol, sitotoksik, HeLa, kanker leher rahim